Sleep quality assessment in chronic rhinosinusitis patients submitted to endoscopic sinus surgery: a meta-analysis - Guttemberg,Manuela Dowsley A. (2019)
Abstract Introduction: Chronic rhinosinusitis can lead to poor sleep quality in affected individuals. Endoscopic nasal surgery has been indicated for patients with chronic rhinosinusitis, resulting in improved quality of life, but it is still unknown if there is a similar improvement in sleep quality after the surgical procedure. Objective: To estimate the sleep quality of patients with chronic rhinosinusitis after undergoing endoscopic sinus surgery. Methods: The literature search was conducted in the indexed databases PubMed, Embase, Lilacs, SciELO, Google Scholar, Web of Science, Scopus, Database of Thesis and Dissertations of CAPES, Cochrane Library, Clinical Trials and in the grey literature. It included studies that reported the sleep quality of patients with chronic rhinosinusitis after undergoing endoscopic sinus surgery based on questionnaires assessing quality of life. Two researchers independently conducted the study selection and extraction. The random effects model was chosen to conduct the meta-analysis that was performed using the statistical package STATA, version 11. Results: Overall, 4 studies and 509 subjects were included in the systematic review. Improved sleep quality was observed in 90% of the patients. There was an improvement (on average, from 57% to 67%) in each of the five symptoms related to sleep quality. The results of the meta-analysis revealed high heterogeneity. Conclusions: This review shows that a large percentage of patients report improved sleep quality after endoscopic sinus surgery.